THE ROLE OF POLITICAL PR IN SOCIETY DEVELOPMENT (Scientific journal of the Fergana State University, 2024)
This article highlights the importance of political PR in communicative processes, controlling individuals, andelection campaigns. One of the most important functions of PR technologies and mass media communications is theanalysis of the role of the political culture in the modernization of society. Also, it is based on examples of the media’srole in the social and political life of the society.